2014
DOI: 10.1177/1046496414551027
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Critique of Partner Effect Research in Small Groups

Abstract: The purpose of this review is to discuss the ways in which partner effects are examined in group contexts. We focus on social influence, as it is a common theme in group research from cognate fields such as communication, psychology, family studies, social psychology, and business. We elaborate on different conceptions of partner effects in our discussion of the social relations model (SRM), the actor-partner interdependence model (APIM), and the group actor-partner interdependence model (GAPIM), and provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 173 publications
(192 reference statements)
1
17
0
Order By: Relevance
“…A long history of actor-group partner research in counseling groups has reported that group members' psychological qualities influence an individual's performance, above and beyond an individual's psychological qualities (Ervin & Bonito, 2014). Such group research has relied on social influence theory, specifically a group actor-partner interdependence model (GAPIM) that conceptualizes individual performance as dependent on group partners' scores (Kenny & Garcia, 2012).…”
Section: Peer Versus Individual Grit Effectsmentioning
confidence: 99%
“…A long history of actor-group partner research in counseling groups has reported that group members' psychological qualities influence an individual's performance, above and beyond an individual's psychological qualities (Ervin & Bonito, 2014). Such group research has relied on social influence theory, specifically a group actor-partner interdependence model (GAPIM) that conceptualizes individual performance as dependent on group partners' scores (Kenny & Garcia, 2012).…”
Section: Peer Versus Individual Grit Effectsmentioning
confidence: 99%
“…On the other hand, if one continuously needs to seek confirmation or if information is not seen as factual until someone else confirms it, these processes may also place stress on employees. For example, according to Ervin and Bonito (2014), one's willingness to participate may diminish if one is being repetitively rejected, and Breaux et al (2008) suggest that the lack of sense of being able to control one's work may threaten wellbeing at work. Consequently, to support well-being construction via work coordination, equal possibilities for participation and acceptance of attendees' various viewpoints are required.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding how group members behave or feel as a function of the others in the group is a critical issue raising different questions regarding the relationship between members and their own group (Ervin & Bonito, 2014;Kenny & Garcia, 2012). The most basic question is the effect of a person's fit into the group or the person's similarity to the other members, but there is also the effect of the group's average, sometimes called group climate, on individuals (Florin, Giamartino, Kenny, & Wandersman, 1990).…”
Section: Pos and Job Performance: Individual Group-level And Individmentioning
confidence: 99%